1997
DOI: 10.1093/jnci/89.16.1207
|View full text |Cite
|
Sign up to set email alerts
|

CYP2E1 Genetic Polymorphisms and Risk of Nasopharyngeal Carcinoma in Taiwan

Abstract: Our findings suggest that the CYP2E1 genotype is a determinant of nasopharyngeal carcinoma risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(144 citation statements)
references
References 31 publications
9
133
1
1
Order By: Relevance
“…Although the literature remains controversial, it has been reported that alterations of GSTM1 and CYP2E1 are associated with a moderate increased risk of NPC [28,29].…”
Section: Gstm1 and Cyp2e1 Polymorphismsmentioning
confidence: 99%
“…Although the literature remains controversial, it has been reported that alterations of GSTM1 and CYP2E1 are associated with a moderate increased risk of NPC [28,29].…”
Section: Gstm1 and Cyp2e1 Polymorphismsmentioning
confidence: 99%
“…Commonly suspected risk factors for NPC include Epstein-Barr virus (EBV) infection, environmental factors, and genetic susceptibility. Associations between NPC risk and certain genetic variations, such as polymorphisms in the CYP2E1 (Hildesheim et al, 1995;Jia et al, 2009) and HLA genes (Tse et al, 2009;Bei et al, 2010), have been suggested by previous studies. EBV has been identified consistently as an important risk factor and in patients with nasopharyngeal carcinoma from regions of high and low incidence, with a dose-response relationship between the EBV antibody level and NPC risk (Chen et al, 1985;Wei and Sham, 2005;Chang and Adami, 2006;Han et al, 2012;Tsao et al, 2014).…”
Section: Discussionmentioning
confidence: 75%
“…CYP2E1 may be less efficiently expressed among carriers of the c2 mutation, making them less susceptible to xenobiotic bioactivation (64). Examination of CYP2E1 variants in nasopharyngeal cancer cases and controls showed an RFLP distribution similar to the Japanese population but higher than in the Finnish or Swedish population (67). A 5-to 7.7-fold increase in cancer risk was found in subjects homozygous for these CYP2E1 variants.…”
Section: Analysis Of Variability and Susceptibilitymentioning
confidence: 65%